2010
DOI: 10.1021/jp106460w
|View full text |Cite
|
Sign up to set email alerts
|

Study of Physical and Chemical Processes of H2 Sensing of Pt-Coated WO3 Nanowire Films

Abstract: H 2 sensors able to operate at room temperature are very important for safe detection of H 2 leakage. We report the large electrical response to H 2 of Pt-coated WO 3 (Pt-WO 3 ) nanowire films without the need of using an external heater. More important, hydrogen sensing processes have been investigated under various conditions, including in air, vacuum filled with pure gas, and a mixture of H 2 and other gases. This is carried out with both electrical and optical methods. The evidence shows that hydrogen will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
50
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(54 citation statements)
references
References 31 publications
4
50
0
Order By: Relevance
“…Among these methods, it is thought to be a good approach that metal oxide materials are decorated by noble metals (e.g. Au [12,13,14], Ag [15,16], Pd [17,18], Pt [19,20]) because of their high-activity and non-structure damage to original species. As the cheapest noble metal and the best conductive metal, Ag decoration does not cause a big increase in material budget and can be used as an ideal additive in lowering the working temperature of metal oxide sensing materials.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, it is thought to be a good approach that metal oxide materials are decorated by noble metals (e.g. Au [12,13,14], Ag [15,16], Pd [17,18], Pt [19,20]) because of their high-activity and non-structure damage to original species. As the cheapest noble metal and the best conductive metal, Ag decoration does not cause a big increase in material budget and can be used as an ideal additive in lowering the working temperature of metal oxide sensing materials.…”
Section: Introductionmentioning
confidence: 99%
“…It is confirmed that Figure 9 The typical I-V characteristics of the MoO 3 NW@Ag NP thin film sensor toward 500 ppm H 2 at room temperature. H 2 molecules were dissociated into H atom on the metal surface [81,82]. The H atom would interact with the preadsorbed oxygen ions (O 2  ) on the surface of MoO 3 , and then a reaction of H and O 2  was taken placed to form H 2 O molecule [83][84][85].…”
Section: Gas Sensing Properties Of the Heteronanostructure Of Silver mentioning
confidence: 99%
“…On the other hand, nanostructure materials tend to reveal extremely distinct properties in comparison with bulk type because of higher surface area and lower dimensionality [11,12]. Nowadays, various WO 3 nanostructured including nanowires [13], nanoplates [14], nanorods [15] and nanoparticles [16] have been synthesized by physical or chemical techniques. Pulsed-laser techniques are bringing the rare opportunity to investigate very interesting phenomena which occur in very short time scale [17].…”
Section: Introductionmentioning
confidence: 99%